MEKANISME PENENTUAN HARGA: PERSPEKTIF EKONOMI SYARIAH - ., Amirah (PERMANA, 2013)
Marketmechanismsisanexchange of goodsandservices and have beengoing on since thebeginningof humancivilization. The importance ofthe marketin Islamcan not be separatedfrom thefunctioning of the marketasan arena forthe sale and purchaseof physicalactivity, butthe rules, normsandissues related tothe market, one of which isthe determination ofthe price. In the concept ofshariaeconomics, determination of priceis doneby consensusbetweensellersandbuyers. In contrasttoconventional economicbargainingdonebythe strengthandability ofeach partyto argue.The basic assumptionused inthis conceptnotonlyto maximizeprofitsorincreasewealthper se,asthere isthe underlying assumptioninthe conventionaleconomy, butmusthave theintentionto help each other, andfacilitatebetween thetwo sides. Interventioncan be doneduring thedetermination of priceconcernsandprotectthe interests ofsociety at large, andthere is noinjured party. Keywords: Price, sharia economic